Effects of study intention and generating multiple choice questions on expository text retention. (April 2019) - Hoogerheide, Vincent; Staal, Justine; Schaap, Lydia; van Gog, Tamara
Abstract: Teachers often recommend their students to generate test questions and answers as a means of preparing for an exam. There is a paucity of research on the effects of this instructional strategy. Two recent studies showed positive effects of generating test questions relative to restudy, but these studies did not control for time on task. Moreover, the scarce research available has been limited to the effects of generating open-ended questions. Therefore, the aim of this study was to investigate whether generating multiple-choice test questions would foster retention (as measured by a multiple-choice test) relative to restudy when time would be kept constant across conditions. Using a 2 × 2 design, university students ( N  = 143) studied a text with the intention of either generating test items or performing well on a test, and then either generated multiple-choice items or restudied the text. Retention was measured by means of a multiple-choice test, both immediately after learning and after a one-week delay. Results showed no effects of study intention. Generating multiple-choice items resulted in lower test performance than restudying the text for the same amount of time. Highlights: We investigated whether generating multiple-choice (MC) test questions would foster retention. University students studied a text and then either generated MC test questions or restudied. Time on task was kept constant and an immediate and delayed posttest administered. Generating MC test questions resulted in lower test performance than restudy. When time is limited, students are better off engaging in restudy or other generative strategies.